HUBUNGAN TINGKAT KEMAMPUANACTIVITIES OF DAILY LIVING(ADL) TERHADAP DISFUNGSI SOSIAL PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA PARE KABUPATEN KEDIRI - Yektiningsih, Erwin (Akademi Keperawatan Pamenang, 2010)
Improving healthy service has given the influence to decrease the death rate of baby and child, increasing thelive of age expectation, the last number of old persons in society to be increase. Increase the number of oldpersons can create manyhealthy of old persons status problem because of decreasing physiologic function ofmany body organ. The purpose of the research to examine the correlation of ADL ability with social disfunctionto the old persons and want to know the kind of social disfunctional that determinant in the old persons. Theresearch design use cross sectional approach by population of old persons at Tresna Werdha Social InstitutionPare-Kediri. Fourthy old persons has been got as sample by simple random sampling technique. There isrelation correlation that significant between ADL ability level with social disfungtion (Pearson correlation testr = 0,465, p= 0,003), to know the assosiation between ADL ability level with social disfungtion kind will beusedMann-Whitney testwhich be gotten result statistically un association between ADL ability level with lowself esteem (p= 0,468) and interpersonal system (p= 0,618). Whereas to the association of ADL ability levelwith the kind of social disfunction performance system statistically show there are significant correlation (p =0,028). From the result can be concluded that there is relation correlation between ADL ability level and socialdisfunction, while ADL ability level with kinerja system there association. Based on thefounded of this researchsuggested in give nursing care comprehensively to older person is needed holistic approach to help adaptionneed to changing of psychologic, social, and spiritual by increasing the ability and potent of the elderly that stillbehad to adapt the change according to the ability